Building A Young Entrepreneur Soul With King Bean - Nasution, Raja Parinsal; Elvina, Elvina; Nasution, Novrihan Leily (CV. Inara, 2022)
Entrepreneurship is a creative and innovative ability that is used as the basis, tips, and resources to find opportunities for success. Having an entrepreneurial spirit means encouraging an independent, creative, innovative, responsible, disciplined mentality, and not giving up easily, like an entrepreneur when starting his business from the bottom. solve the problem at hand. 1. Preparation stage 2. Availability of supporting tools The method of implementing community service regarding Building a Young Entrepreneurial Spirit with Kacang Raja consists of: 1. Material preparation 2. Service techniques in the form of socialization/introduction and discussion as well as manufacturing training. 3. Community service time will be held on January 21, 2022. In order to find out the understanding of the implementation of community service, the writing team distributed a questionnaire/questionnaire related to the level of community understanding of the implementation of community service through outreach activities. exploration of 20 respondents. SMEs can be developed sustainably through improving people (improvement of human resources quality), process (optimization of work processes and services), product (quality of goods), and technology (utilization of technology) which will ultimately generate better profits.